The Dangers of Diversity: Heresy and Authority in the 1405 Case of John Edward - Forrest, Ian (Studies in church history, 2007)
When John Edward of Brington in Northamptonshire abjured heresy in the ‘Greneyerd’ of Norwich cathedral close on Palm Sunday 1405, he was presented to the gathered crowds as a living example of the dangers of diversity in the Christian faith. Because heresy was feared as a fundamental challenge to doctrine, authority, and social harmony, the agents of Church and crown went to great lengths in the period between 1382 and the Reformation to advertise its depravity and illegality. The anti-heresy message was not, however, a simple one, and the judicial performances that constitute the Church’s propaganda campaign on this issue sometimes used highly equivocal rhetoric and images. In these performances heresy was capable of being represented as a minority sectarian problem, or one diffused throughout society. In truth it was both, and so the anti-heresy message had to encompass much more nuance than one might imagine. This essay focuses on the campaign against the lollards in late medieval England, in particular John Edward’s staged abjuration, which is recorded in a letter sent by the presiding bishop, Henry Despenser, to his archbishop, Thomas Arundel. This certification presents a compelling tableau vivant encompassing the penitent, the crowds, and the authorities of Church, crown, and city. In their efforts to stage-manage the abjuration of heresy, however, these authorities had not only to navigate the complexity of anti-heretical rhetoric and present it to a large audience, but, perhaps more importantly, had to overcome considerable rancour and division within their own ranks, to present a unified front against the threat of heresy. For they had to show diat there was a unity from which heretics were deviating. Edward’s abjuration, therefore, offered an important opportunity to demonstrate repentance, and to invite the clergy and people of Norwich to consider the dangers posed by their own tendencies towards disunity.